2018
DOI: 10.1002/gps.5039
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation improves the frontal cognitive function of older adults

Abstract: Objectives The frontal lobe hypothesis of age‐related cognitive decline suggests that the deterioration of the prefrontal cortical regions that occurs with aging leads to executive function deficits. Photobiomodulation (PBM) is a newly developed, noninvasive technique for enhancing brain function, which has shown promising effects on cognitive function in both animals and humans. This randomized, sham‐controlled study sought to examine the effects of PBM on the frontal brain function of older adults. Methods/d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
56
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(80 citation statements)
references
References 74 publications
4
56
0
1
Order By: Relevance
“…PBMT is widely used to treat a variety of medical conditions such as wound healing, pain and inflammation, diabetic ulcers, blood disorders, musculoskeletal complications, coronary artery disease as well as tissue repair and regeneration (Chung et al, 2012;Arany et al, 2014). Moreover, PBMT has steadily attracted increasing interest for a wide range of applications to the brain, ranging from neurotrauma, neurodegeneration, and neuropsychiatric disorders to enhance brain functions in healthy individuals (Salehpour et al, 2018b;Caldieraro and Cassano, 2019;Chan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…PBMT is widely used to treat a variety of medical conditions such as wound healing, pain and inflammation, diabetic ulcers, blood disorders, musculoskeletal complications, coronary artery disease as well as tissue repair and regeneration (Chung et al, 2012;Arany et al, 2014). Moreover, PBMT has steadily attracted increasing interest for a wide range of applications to the brain, ranging from neurotrauma, neurodegeneration, and neuropsychiatric disorders to enhance brain functions in healthy individuals (Salehpour et al, 2018b;Caldieraro and Cassano, 2019;Chan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Chan et al observed improved frontal cognitive function in older human volunteers (≥60 years) after a single session of PBM [44]. The device used in their study consisted of three LED cluster heads with a mix of 633 nm and 870 nm diodes and a power density of 44.4 mW/cm 2 .…”
Section: Applications Of Transcranial Photobiomodulation To Human Submentioning
confidence: 99%
“…It has been shown to activate neurons, promote their metabolic activity, improve the local microenvironment at the site of injury and accelerate axonal growth. In recent years, PBM has been broadly applied in therapy for brain injury and other cerebral diseases such as stroke and neurodegenerative disorders, where it has yielded encouraging results . Similarly, research on SCI has revealed that PBM can suppress the activation of immune cells at the site of injury, reduce the expression of proinflammatory factors and chemokines and reduce the incidence of secondary SCI, as well as promote the large‐scale regrowth of nerve fibers at the site of injury and significantly improve the recovery of locomotor function .…”
Section: Introductionmentioning
confidence: 99%